KOMUNIKASI DISABILITAS: MEMAHAMI HAMBATAN KOMUNIKASI DAN SOCIAL SUPPORT PEGAWAI FRONTLINE TULI DI LINGKUNGAN KERJA DENGAR - Sheila Rafa Azzahra; S. Rouli Manalu; Hedi Pudjo Santosa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Apart from the communication limitations Deaf people have, some of them still have economic needs that must be met. In Indonesia, there are Deaf people who work as frontliners in normal working environments. As Deaf frontline employees, working in a normal work environment can create potential barriers to communication while working. To be able to deal with these barriers, it takes the role of other people and the environment as social support. This study aims to understand communication experiences, communication barriers, and forms of social support that Deaf frontline employees receive in a normal working environment. This study used Interpretative Phenomenological Analysis (IPA) method with in-depth interview techniques with four Deaf people who work as frontliners in normal working environment. This research refers to the concept of Communication Barriers by Orbe & Bruess and Social Support Behavior Codes which is a framework by Cutrona & Suhr. The results of this study found that Deaf people who work as frontliners communicate verbally (sign language and writing) and nonverbally (gestures). Deaf frontline employees have positive, encouraging experiences in the form of disability-friendly facilities and colleagues who can speak sign language. However, at the same time, Deaf frontline employees also experienced negative experiences in the form of discriminatory treatment, cynical treatment, and rejection from customers, also bullying from colleagues. During communication in the normal work environment, communication barriers arise such as lip reading which is hindered by masks (physical barriers), speaking too fast and differences in sign language (semantic barriers), hearing loss (physiological barriers), and lack of confidence (psychological barriers). Finally, social support appears in the form of action-facilitating support and nurturing support in the form of giving advice, translation and changing work roles by deaf frontline co-workers, praise for work, alleviating feelings of guilt, being listened to when venting, and the presence of co-workers.